Family dairy farms in the Podlasie province, Poland: farm typology according to farming system - Castel, J. M.; Madry, W.; Gozdowski, D.; Roszkowska-Madra, B.; Dabrowski, M.; Lupa, W.; Mena, Y. (Spanish Journal of Agricultural Research, 2010)
The aim of this paper is to establish a farm typology according to the dairy farming systems in the western part of the Podlasie province. Data of 39 variables was collected by a survey to owners of 123 family farms. A two-stage multivariate analysis was conducted in order to determine farm typology. Three principal components were detected, explaining 80.4% of the total variance. The cluster analysis identified five groups of farms. In two groups the cow productivity is the biggest in the area. A third group contains the smallest and lowest cow productivity farms, with high proportion of non-agricultural activities. One of the two remaining groups has better soil quality and medium cow productivity. The other group has low or medium soil quality but cow productivity is higher than in the fourth group. The SWOT analysis shows different weaknesses and strengths for different groups, as well as those common to a larger number of groups. Weaknesses are related to small farm size, large number of workers, low or medium soil quality and low or medium level of technology. Strengths are related to a large share of fodder crops, low livestock density, diversification of agrarian activities and acceptable cow productivity. On the other hand, general opportunities are linked to the EU-CAP evolution and to the presence of cooperatives in the region, whereas general threats derive from a hypothetic increase of feed prices and quantity of milk produced in the EU, which could lead to a fall in milk prices.